Evaluasi Penerapan Pupuk Kandang Ayam Pedaging Pada Usahatani Sayuran Segar Semi Organik di Kecamatan Lingsar - Tajidan Tajidan; Arifuddin Sahidu; Halil Halil; Suparmin Suparmin; Ria Ristina (Jurnal Gema Ngabdi, 2022)
use of organic fertilizer sourced from animal waste has long been practiced by farmers in the Bug-bug Village area. The fertilization technique and the dose used are based on their own experience or the experience of other farmers, so it is necessary to evaluate. The method used in the evaluation was the demonstration plot method with two treatments and two types of fresh vegetables, namely pulled spinach and mustard caisim. In the first treatment, manure was immersed and sprinkled on the top layer of soil with a dose of 6,534 tons/ha; In the second treatment, manure was only sprinkled on the top layer of the soil at a dose of 3,267 tons/ha. The evaluation results show that fertilizing broiler manure on amaranth farming with the technique of immersing and sprinkling on top of the soil layer at a dose of 6.534 tons/hectare resulted in higher production, while its application to caisim mustard farming resulted in lower production, but technical fertilization by sprinkling fertilizer Broiler cages at the top of the soil layer with a dose of 3,267 tons/hectare resulted in higher caisim mustard production than the fertilizer technique treatment by immersing and sowing at the top of the soil layer at a dose of 6,534 tons/hectare.